Reactive oxygen species-independent activation of the IL-1β inflammasome in cells from patients with chronic granulomatous disease - van de Veerdonk, Frank L; Smeekens, Sanne P; Joosten, Leo A.B; Kullberg, Bart Jan; Dinarello, Charles A; van der Meer, Jos W.M; Netea, Mihai G (Proceedings of the National Academy of Sciences - PNAS, 2010)
Humans with chronic granulomatous diseases (CGDs) due to mutations in p47-phox have defective NADPH activity and thus cannot generate NADPH-dependent reactive oxygen species (ROS). The role of ROS in inflammation is controversial; some in vitro studies suggest that ROS are crucial for secretion of IL-1β via inflammasome activation, whereas mice defective for ROS and patients with CGD have a proinflammatory phenotype. In this study, we evaluated activation of the IL-1β inflammasome in cells from CGD patients. In contrast to previous studies using the small molecule diphenylene iodonium (DPI) as a ROS inhibitor, we found no decrease in either caspase-1 activation or secretion of IL-1β and IL-18 in primary CGD monocytes. Moreover, activation of CGD monocytes by uric acid crystals induced a 4-fold higher level of IL-1β secretion compared with that seen in monocytes from unaffected subjects, and this increase was not due to increased synthesis of the IL-1β precursor. In addition, Western blot analysis of CGD cells revealed that caspase-1 activation was not decreased, but rather was increased compared with control cells. Examination of the effects exerted by the inhibition of ROS activity by DPI revealed that the decrease in IL-1β secretion by DPI was actually due to inhibition of IL-1β gene expression. Thus, inconsistent with the proinflammatory role of ROS, the present findings support the concept that ROS likely dampen inflammasome activation. The absence of ROS in CGD monocytes may explain the presence of an inflammatory phenotype characterized by granulomas and inflammatory bowel disease occurring in CGD patients.